Sulforaphane induces cytotoxicity and lysosome- and mitochondria-dependent cell death in colon cancer cells with deleted p53 - Rudolf, Emil; Cervinka, Miroslav (Toxicology in vitro, 2011)
Mechanisms and pathways responsible for cytotoxicity of sulforaphane (SF) in colon cancer cells with deleted p53 were investigated during 48 h of exposure. SF showed dose-dependent cytotoxicity and proapoptotic activity in the present model. In addition, in HCT-116 p53KO cells SF induced DNA damage with the subsequent cellular response and signaling not including p53 and caspase-2 pathways. Conversely, in SF-treated cells JNK was activated which led to an early lysosomal membrane permeabilization, release of cathepsin B and D and activation of Bid by specific cleavage. Concomitantly, the expression of Bax increased in the presence of JNK-mediated Bcl-2 inhibition which was followed by mitochondrial release of cytochrome c and activation of apoptosis. These results suggest that SF may be useful as a chemopreventive agent in colon cancer with inactivated or lost p53.
Keywords: regulace genové exprese u nádorů; Anticarcinogenic Agents; Tumor Suppressor Protein p53; Stress, Physiological; sulfoxidy; proliferace buněk; DNA Damage; Lysosomes; Isothiocyanates; Mitochondria; lyzozomy; HCT116 buňky; MAP kinasa-kinasa 4; delece genu; thiokyanatany; Gene Expression Regulation, Neoplastic; Heat-Shock Proteins; Time Factors; časové faktory; nádory tračníku; lidé; HCT116 Cells; isothiokyanatany; Sulfoxides; Thiocyanates; protein X asociovaný s bcl-2; MAP Kinase Kinase 4; antikarcinogenní látky; fyziologický stres; mitochondrie; Colonic Neoplasms; poškození DNA; Gene Deletion; nádorový supresorový protein p53; Cell Proliferation; Cell Survival; bcl-2-Associated X Protein; viabilita buněk; proteiny teplotního šoku; Humans